The effectiveness of price limits in the South African white maize futures market. Issue 3 (3rd July 2018) - Sayed, Ayesha; Auret, Christo
ABSTRACT: Futures markets perform two essential functions by creating a platform for price discovery and permitting low cost hedging of risk. Some futures markets impose limits on the amount asset prices can change within a trading day to prevent the market from overreacting. While the objective of price limits may be to dampen volatility, many argue that they are instead self-fulfilling, create a 'magnetic effect' and amplify volatility. This magnet or gravitation effect causes trading volume and price variability to increase as market participants panic and advance the execution of their trades. This paper empirically investigates the effectiveness of price limits using daily data for 40 white maize futures contracts over the period March 2010 to December 2017. Four issues predominant in the circuit breaker literature are examined: the volatility spillover hypothesis, the delayed price discovery hypothesis, the liquidity interference hypothesis and the magnet/gravitation effect hypothesis. Most of the empirical evidence presented in the paper indicates that for white maize futures, price limits may be ineffective.